Influence of Financial Performance Indicators on Stock Prices: A Study of Food and Beverage Firms on the Indonesian Stock Exchange - Devina, Koming Melia; Adiandari, Ade Maharini (Countable (Contemporary Business and Sustainability Science), 2024)
This study aims to determine the effect of Return on Assets (ROA), Return on Equity (ROE), and Earning Per Share (EPS) on stock prices in food and beverage sub-sector companies listed on the Indonesian Stock Exchange for the period 2016 - 2021. The approach of this study was quantitative analysis technique. Secondary data was the source of this study. The population used in this study amounted to 45 companies. Samples were taken using purposive sampling method and obtained 12 companies as samples. The data analysis used the classical assumption test, multiple linear regression analysis, and to test the hypothesis, the researcher used the partial significance test (t-test) and simultaneous significance test (F-test). The result showed that simultaneously Return on Asset (ROA), Return on Equity (ROE), and Earning Per Share (EPS) has a significant effect on stock prices. Partially Return on Equity (ROE) and Earning Per Share (EPS) have a significant effect on stock prices, while Return on Assets (ROA) have no significant effect on stock prices.